IDENTIFIKASI HEWAN RESERVOIR LEPTOSPIROSIS DI DAERAH PENINGKATAN KASUS LEPTOSPIROSIS DI DESA PAGEDANGAN ILIR, KECAMATAN KRONJO, KABUPATEN TANGERANG TAHUN 2015 - Arum Sih Joharina; Dimas Bagus Wicaksono Putro; Aryo Ardanto; Arief Mulyono; Wiwik Trapsilowati, SKM, M.Kes (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2018)
In Indonesia, leptospirosis often causes outbreaks. Three important sources of transmission of leptospirosis are the environment contaminated with leptospira, the presence of rats and presence of livestock as reservoirs. This study aims to determine the reservoir that plays a role in the leptospirosis transmission in increased case areas of leptospirosis in the Pagedangan Ilir Village, Kronjo Sub-district, Tangerang. Rat traping was done twice. Each trapping was done two times, in consecutive days. Livestock sampling was also conducted in the study area. Rat and livestock serum specimens were collected for leptospirosis detection using MAT, while rat kidneys were collected for PCR test. Leptospirosis detection was performed by PCR and MAT. The results of the first and second rat traping showed relative density of 17% and 20% in the houses, as well as 14% and 10% in outdoor area. Rat traped consist of two species, Rattus norvegicus and Rattus tanezumi. The prevalence of pathogenic leptospira in rat (with PCR assay) was 33% in the first trap and 26% in the second trap. The MAT test showed a positive 14% on R. norvegicus in the first trap, but negative in the second trap. While livestock did not show PCR positive, but one serological positive sample (by MAT) with low titers (1:20) was found against the serovar Robinsoni